Managing New Products Successfully:A Strategic Imperative - Ranjan, Rajeev Kumar (Indian Journal of Marketing, 2009)
For any company to push its new product to consumers in a particular time, advertisements are just not enough. Innovative sales promotion techniques are also needed to suit various products. The paper primarily focuses on the abilities of the organizations to manage innovative products all through the product life cycle. The paper aims at highlighting the strategies which product manager should develop for getting the best out of the innovative products. This Paper extends Emotional marketing Conceptual model for brand management by relating different stages of the product life cycle that consumers engage in.